Raine Eye Health Study: Design, Methodology and Baseline Prevalence of Ophthalmic Disease in a Birth-cohort Study of Young Adults. (10th January 2013) - Yazar, Seyhan; Forward, Hannah; McKnight, Charlotte M.; Tan, Alex; Soloshenko, Alla; Oates, Sandra K.; Ang, Wei; Sherwin, Justin C.; Wood, Diane; Mountain, Jenny A.; Pennell, Craig E.; Hewitt, Alex W.; et al.
ABSTRACT: Purpose: The Raine Eye Health Study (REHS) was conceived to determine the prevalence of and risk factors for eye disease in young adults, and to characterize ocular biometric parameters in a young adult cohort. This article summarizes the rationale and study design of REHS and outlines the baseline prevalence of ophthalmic disease in this population. Methods: The Western Australian Pregnancy Cohort (Raine) Study originated as a randomized-controlled trial of 2900 women recruited from the state's largest maternity hospital. Their offspring ( N = 2868) have been followed at birth, ages 1, 2, 3, 5, 8, 10, 14, 17 and 20 years of age in a prospective cohort study. DNA has been collected from participants for genome-wide association studies. At the 20-year follow-up participants completed a comprehensive eye assessment that included visual acuity, orthoptic assessment and cycloplegic autorefraction, as well as several ocular biometric variables and multiple ophthalmic photographs of the anterior and posterior segments. Results: A total of 1344 participants (51.3% male) were assessed over a 24-month period. For the majority of examined participants (85.5%) both parents were Caucasian, 63.3% had completed school year 12 or equivalent, 5.5% had myopia (spherical equivalent ≤−3 diopters) and 15 participants (1.2%) had unilateral or bilateral pterygia. Keratoconus, cataract, keratitis and uveitis were rare. Conclusion: The REHS design and methodology allow comparison with other population-based studies of eye disease. The study established the prevalence of eye disorders in a large sample of predominantly Caucasian young Australian adults.